The effects of stress exposure on prefrontal cortex: Translating basic research into successful treatments for post-traumatic stress disorder - Arnsten, Amy F.T. (Neurobiol Stress, 2014)
Research on the neurobiology of the stress response in animals has led to successful new treatments for Post-Traumatic Stress Disorder (PTSD) in humans. Basic research has found that high levels of catecholamine release during stress rapidly impair the top-down cognitive functions of the prefrontal cortex (PFC), while strengthening the emotional and habitual responses of the amygdala and basal ganglia. Chronic stress exposure leads to dendritic atrophy in PFC, dendritic extension in the amygdala, and strengthening of the noradrenergic (NE) system. High levels of NE release during stress engage low affinity alpha-1 adrenoceptors, (and likely beta-1 adrenoceptors), which rapidly reduce the firing of PFC neurons, but strengthen amygdala function. In contrast, moderate levels of NE release during nonstress conditions engage higher affinity alpha-2A receptors, which strengthen PFC, weaken amygdala, and regulate NE cell firing. Thus, either alpha-1 receptor blockade or alpha-2A receptor stimulation can protect PFC function during stress. Patients with PTSD have signs of PFC dysfunction. Clinical studies have found that blocking alpha-1 receptors with prazosin, or stimulating alpha-2A receptors with guanfacine or clonidine can be useful in reducing the symptoms of PTSD. Placebo-controlled trials have shown that prazosin is helpful in veterans, active duty soldiers and civilians with PTSD, including improvement of PFC symptoms such as impaired concentration and impulse control. Open label studies suggest that guanfacine may be especially helpful in treating children and adolescents who have experienced trauma. Thus, understanding the neurobiology of the stress response has begun to help patients with stress disorders.